Within and across country variations in treatment of patients with heart failure and diabetes. (19th August 2021) - Or, Zeynep; Shatrov, Kosta; Penneau, Anne; Wodchis, Walter; Abiona, Olukorede; Blankart, Carl Rudolf; Bowden, Nicholas; Bernal‐Delgado, Enrique; Knight, Hannah; Lorenzoni, Luca; Marino, Alberto; Papanicolas, Irene; et al.
Abstract: Objective: To compare within‐country variation of health care utilization and spending of patients with chronic heart failure (CHF) and diabetes across countries. Data Sources: Patient‐level linked data sources compiled by the International Collaborative on Costs, Outcomes, and Needs in Care across nine countries: Australia, Canada, England, France, Germany, New Zealand, Spain, Switzerland, and the United States. Data Collection Methods: Patients were identified in routine hospital data with a primary diagnosis of CHF and a secondary diagnosis of diabetes in 2015/2016. Study Design: We calculated the care consumption of patients after a hospital admission over a year across the care pathway—ranging from primary care to home health nursing care. To compare the distribution of care consumption in each country, we use Gini coefficients, Lorenz curves, and female–male ratios for eight utilization and spending measures. Principal Findings: In all countries, rehabilitation and home nursing care were highly concentrated in the top decile of patients, while the number of drug prescriptions were more uniformly distributed. On average, the Gini coefficient for drug consumption is about 0.30 (95% confidence interval (CI): 0.27–0.36), while it is, 0.50 (0.45–0.56) for primary care visits, and more than 0.75 (0.81–0.92) for rehabilitation use and nurse visits at home (0.78; 0.62–0.9). Variations in spending were more pronounced than in utilization. Compared to men, women spend more days at initial hospital admission (+5%, 1.01–1.06), have a higher number of prescriptions (+7%, 1.05–1.09), and substantially more rehabilitation and home care (+20% to 35%, 0.79–1.6, 0.99–1.64), but have fewer visits to specialists (−10%; 0.84–0.97). Conclusions: Distribution of health care consumption in different settings varies within countries, but there are also some common treatment patterns across all countries. Clinicians and policy makers need to look into these differences in care utilization by sex and care setting to determine whether they are justified or indicate suboptimal care.